"What Matters to Me": What pediatric stem cell transplant patients want their providers to know. Issue 4 (13th July 2021) - Brand McCarthy, Sarah; Tarquini, Sarah J.; Metcalf, Brittany; , Lucy Pickard; Greenzang, Katie A.; Mack, Jennifer
Abstract: Objectives: Engagement of pediatric patients in conversations about their healthcare can lead to better psychological and physical outcomes. We used a communication tool called "What Matters to Me" (WMTM) to provide insight into what seriously ill children want to tell their healthcare providers about what is important to them. Research Approach: Content analysis of completed tools Participants: 21 pediatric patients hospitalized on a stem cell transplant unit. Methodological Application: Direct content analysis. Findings: Three themes were identified: importance of personal identity, preferences for communication, and preferences for care delivery. Interpretations: Children and adolescents with serious medical illnesses are willing to share what matters to them with members of their care team. WMTM provides an opportunity for pediatric units to systematically offer this opportunity to pediatric patients. Findings for Psychosocial Providers: Children and adolescents are able to identify and share what matters to them with their healthcare providers, providing an opportunity for engagement in medical care.